Role of differential gene expression in the occurrence and development of diabetic nephropathy - Chen Li-ting; Yue Rui; Wang Xi-yue; Kong Fan-wu (Linchuang shenzangbing zazhi)
Objective The pathogenesis of diabetic nephropathy is rather complex.It is an abnormal metabolic process involving multiple genes and multiple steps.Therefore it is necessary to search for genes playing a key role in the occurrence and development of diabetic kidney disease（DKD）.Methods Bioinformatic was utilized for selecting the relevant data of DKD.And R software was employed for conducting differential gene screening for locating the key genes affecting DKD.Results There were 133 differential genes screened in GSE30528,704 differential genes in GSE1009 and 134 differential genes in GSE30529.Moreover, these genes are generally involved in renal development, collagen trimer aggregation, complement and coagulation cascade and AGE-RAGE signaling.Conclusion The genes VEGFA,MAGI2 and NPHS1 involved in the differentiation of glomerular filtering cells affect the glomerular structural changes in DKD;Genes S100 A9,FCER1 G,C3 AR1,CXCL1,ITGB2,COL1 A2 and LUM involved in tubulointerstitial inflammatory cell activation and collagen formation affect tubulointerstitial fibrosis in DKD;COL4 A3 and its family genes of AGE-RAGE signaling pathway, as well as F2 R,F5,F3,C3 genes of complement and coagulation cascade reaction are involved in the development of DKD.